The Issue of Land Criminal Offenses - Alfons Alfons; Mujiati Mujiati; Dian Aries Mujiburohman (Syiar Hukum, 2022)
Criminal provisions in land law/UUPA have not been regulated explicitly, on the other hand, the land authority does not have the authority to enforce the law for people or legal entities that do not use land according to their obligations. Based on this, this research aims to examine the criminal provisions in Article 52 of the UUPA which regulates the obligation to maintain land for individuals or legal entities. The research method used is normative legal research. The findings of this study are that the implementation of Article 52 of the UUPA is not applied and generally administrative sanctions are used such as revoking or canceling land rights, but the revocation or cancellation of land rights has the consequence of filing a lawsuit in court by the right holder, the provisions for sanctions for violating confinement or fines are not applied. The lack of firm regulation and enforcement of the law has resulted in the concentration of land tenure for both investment and personal interests increasing, resulting in the non-fulfillment of a sense of justice, welfare, and productive and efficient use of land, and unmaintained soil fertility resulting in land damage.